Insights Into Veterans' Perspectives on a Peer Support Program for Glycemic Management. Issue 6 (December 2019) - Lott, Briana D.; Dicks, Tanisha N.; Keddem, Shimrit; Ganetsky, Valerie S.; Shea, Judy A.; Long, Judith A.
Purpose: The purpose of this study was to explore the mentor-mentee relationship in veterans with type 2 diabetes and gain insight into successful pairings. Methods: Qualitative semistructured interviews were conducted as part of a peer mentoring randomized controlled trial to understand participants' experiences, their relationship with their partner, and how the intervention affected self-care behaviors. Purposive sampling was done to ensure adequate representation of mentees who made large strides in reaching their glycemic targets, those who made marginal improvements toward their glycemic goals, and those who got worse. All interviews were audio-recorded, transcribed, and analyzed for salient themes. Results: The intervention was well received, with most participants describing it as valuable. Participants perceived the intervention to have a number of benefits, including accessible support, enhanced self-confidence, increased accountability, better self-efficacy, improved glycemic management, and a fulfilled sense of altruism. Participants did encounter barriers, including logistical, interpersonal, and individual obstacles. The more successful mentees tended to be more effusive in their description of their mentors, endorsed a stronger sense of connection to their mentor, described a more structured interaction with their mentor, and tended to be more complimentary of the intervention. Conclusions: Large peer support programs are appealing and well received. These programs can be optimized by selecting naturally inclined mentors, providing additional training to introduce more structure into mentorship interactions, and targeting mentees who are not struggling with overwhelming comorbidities.